Nanobiomaterials - Yi, Dong Kee (CRC Press, 2017)
Includes bibliographical references; Bio-inspired magnetic nanoparticles / G.C. Papaefthymiou and E. Devlin -- Nanoparticles for bio-imaging / Yongtaik Lim -- Biomedical applications of dendrimer porphyrin or phthalocyanine / Woo Dong Jang -- Polymeric nanoparticles in cancer therapy / Kwangmeyung Kim -- Fullerene and carbon nanotube bioconjugates / S. Samal -- Biocatalytic nanosystems / Suseong Lee -- Magnetically induced hyperthermia for biomedical applications / M. Fardis [and others] -- Engineered biomolecules as nanomaterials / Kitae Nam -- Microfluidic based polymer scaffold design for tissue engineering / Sanghyo Kim -- Fabrication of mobile hybrid microswimmers using micro/nanoparticles and bacterial flagella / Min Jun Kim -- Environmental applications of nanomaterials / Chang Ha Lee -- Cytotoxicity of biosynthesized nanomaterials and functionalized nanomaterials : use in therapy / Kyu Sik Yun